Abstract depiction of human figures in impressionist art and children's picture books. Issue 1 (June 2019) - Dodgson, Neil A.
Highlights: Humans are able to recognise extremely abstract human figures. Children's picture books give excellent examples of how artists achieve abstraction. Textural detail can alter considerably between levels of abstraction. Abstraction of human figures requires model-based understanding. The principal challenge in automating such abstraction is replicating human knowledge of the world. Graphical abstract: Abstract: The human figure is important in art. I discuss examples of the abstract depiction of the human figure, from both impressionist painting and children's book illustration, and the challenge faced in algorithmically mimicking what human artists can achieve. I demonstrate that there are excellent examples in both genres that provide insight into what a human artist sees as important in providing abstraction at different levels of detail. The challenge lies in the human brain having enormous knowledge about the world and an ability to make fine distinctions about other humans from posture, clothing and expression. This allows a human to make assumptions about human figures from a tiny amount of data, and allows a human artist to take advantage of this when creating art. The question for the computer graphics community is whether and how we could algorithmically mimic what a human artist can do. I provide evidence from both genres to suggest possible ways forward.